Persian compounds in the mental lexicon - Yousefzadeh, Bahareh; Libben, Gary; Segalowitz, Sidney J. (Frontiers in Communication, 2024)
Compound words exhibit properties of both single words and phrases, raising the question of the extent to which compounds are processed as single units or as word combinations. Most studies have addressed this in Germanic languages (English, German and Dutch) which have the similar compound structure of modifier-head ordering. To see whether this limits our understanding of compound word processing and to examine compound decomposition in another language, we presented Persian stimuli auditorily in a paradigm involving typing out stimuli. We examined the effects of semantic transparency, modifier-head ordering and the potential differences between attached compounds written without spaces and those with a space between the constituents.We report the inter-keystroke-interval times, yielding letter-by-letter production of compound structures produced by 31 native speakers of Persian. Results analyzed in a linear mixed-model regression analysis suggested that, for all compounds, typing speed is slowed at the boundary between the constituents of Persian compound words. These effects, which we interpret to be evidence of morphological decomposition, were present for both semantically transparent and opaque compounds, for both head-initial and head-final compounds, and for both attached and spaced compounds.We observed greater morphological decomposition effects in semantically transparent (versus opaque) compounds. We also observed that the way transparency influences the degree of decomposition is moderated by headedness. Thus, this first report for the written production of compound words confirms previous observations of significant decomposition at morphological boundaries in English compounds, but with variation specific to Persian.